On Generalized Î²-Open Sets in Ideal Bitopological Space - Bukhatwa, Ibtissam; Demiralp, Sibel (New York Business Global LLC, 2020)
In this article, we introduce and study the concepts of Î³ij -semi-I-open sets and Î³ij -Î²I-open sets by generalizing (i, j)-semi-I-open sets and (ij)-Î²I-open sets, respectively, in ideal bitopological spaces with an operation Î³ : Ï„ â†’ P(X). Further, we describe and study (Î³, Î´)ij -semi-I-continuous and (Î³, Î´)ij -Î²I-continuous functions in ideal bitopological spaces and their related notions. In addition, various examples and counterexamples are given for answers to some questions raised in this study.